KETERBACAAN ARTIKEL EDUKASI TBC DI WEBSITE KEMENKES RI: (Readability Research dengan Formula Flesch Reading Ease dan Cloze Procedure di Kalangan Tenaga Kesehatan) - Muhammad Ilham Tri Setyo; Sri Wijayanti (Jurnal Komunikasi & Media Digital, 2024)
The purpose of this study is to describe the readability of TB educational articles from the Indonesian Ministry of Health. TB educational articles are an effort to improve health literacy among health workers which is still low. For this reason, the formulation of this research problem is to find out the level of readability of three educational articles on handling tuberculosis disease at www.kemkes.go.id for the 2023 period using the Flesch reading ease formula and the cloze procedure. The concepts used include Shannon and Weaver's information theory, readability theory, and health education articles. This research is a descriptive type of quantitative research. The method used is readability with the Flesch reading ease formula and cloze procedure. Respondents were selected from health workers because they are the parties involved in handling TB disease. The results showed that the readability level of three articles with flesch reading was very difficult, with scores between -49.965 and -17.378. The low readability of the articles is thought to be due to the incompatibility of the reading language with the formula used. In comparison, the level of readability with the cloze procedure shows a very easy category with a score between 665 and 694. This means that the reading is very easy for health workers to understand in general. Some factors affect their readability level, including gender, experience with reading material, and respondents' knowledge of the use of the Indonesian language in reading.